Impact of coach-athlete relationship to UiTM Negeri Sembilan athlete's performance / Muhammad Munir Faizal - Faizal, Muhammad Munir (2017)
This study was to identify the impact of coach-athlete relationship to UiTM Negeri Sembilan athlete performance. A survey used the questionnaire that is approached to I 78 of UiTM Negeri Sembilan athlete. The respondents were chosen using the random sampling technique. The instruments consist of three sections which is demographic profile, Coach-Athlete Relationship Questionnaire (CART-Q) and 3x2 achievement goals questionnaire for sport (3x2 AGQ-S). this researched three main purposes, which are: (I) To identify the demographic profile for UiTM Negeri Sembilan athletes; (2) To identify the dimension of coach-athlete relationship; and (3) To determine the impact of coach athlete relationship towards UiTM Negeri Sembilan athlete performance. This study utilized Descriptive analysis and Pearson Correlation. This study also found that demographic profile variables of: (1) Gender; (2) age; (3) programme; (4) involvement in sport; and (5) level of participation. For Coach-Athlete Relationship that are consist 23 question and involved 3 dimension which are: (l) closeness; (2) commitment; and (3) complement.